Beyond the causes: Rethinking mitigating measures to avert cost and time overruns in construction projects. Issue 3 (10th July 2017) - Asiedu, Richard Ohene; Adaku, Ebenezer; Owusu-Manu, De-Graft
Abstract : Purpose: This paper aims to contend that the circle of investigation into overruns cannot be complete unless the established critical failure factors are matched against their respective mitigating measures to avert the overruns. Extant literature is replete with factors that engender cost and time overruns within the design and construction phase. The constraint is the lack of a scientific approach in establishing a tackling mechanism to address the root causes and stakeholder responsibilities. Design/methodology/approach: The research is based on nine unique grand factors previously established and reported in literature about the Ghanaian Construction Industry. A focus group discussion convened through a purposive sampling technique led to the establishment of a list of mitigating measures and strategies. Findings: The paper established a checklist of 114 mitigating measures categorised into preventive, predictive and corrective approaches. Additionally, several short to medium term key strategies have been recommended to avert the occurrence of cost and time overruns. Originality/value: The mitigating measures can be adopted as a checklist of good practice to help practitioners enhance the effectiveness of project budget and schedule control. It is also supposed to serve as a guide to practitioners in averting overruns through predictive, preventive and/or corrective causes. A unique approach in averting the occurrence of cost and time overruns.